Peranan Kepala Sekolah dalam Meningkatkan Kinerja Sumber Daya Manusia di SMAN 1 Bululawang Kabupaten Malang - Iwan Agus Famuji; Rukin Rukin; Ady Setiawan (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study examines the influence of school leadership on improving the quality of human resources within educational institutions by implementing character- and environment-focused programs, specifically the Adiwiyata School initiative. Employing a qualitative methodology, data were gathered through interviews, observations, and document analysis across several schools participating in the program. The results reveal that transformational leadership plays a critical role in motivating teachers and staff to enhance their professional skills and adopt innovative teaching approaches rooted in environmental stewardship and national character values. Additionally, active collaboration between schools and local communities emerges as a key factor contributing to the program’s effectiveness. The Adiwiyata School program not only fosters heightened environmental consciousness but also cultivates a school culture dedicated to developing student character. The study concludes that effective leadership in human resource management and school governance is essential for fostering sustainable, positive transformation, particularly within the evolving educational landscape influenced by digital advancements and pandemic challenges. These findings provide valuable insights for formulating adaptive and sustainable policies and management strategies in education.